Reproductive Health Education Study Materials for Junior High School Students - Rochmayani, Dewi Sari; Zulaekha, Chusnul (Journal of Health Education, 2019)
Background: Some indicators of reproductive health education in schools have not reached the expected level. A preliminary study on junior high school students shows that 90% of students have poor reproductive health knowledge. This situation is an indicator of the weak reproductive health education in junior high schools. Methods: The design of this study is research and development. The study continued with field tests on 30 junior high school teachers in the Mijen sub-district of Semarang City. Results: The study succeeded in formulating 5 materials and 18 study materials on reproductive health education for junior high school students. The material includes: 1) Male and female reproductive organs, 2) Personal protection from sexual abuse, 3) Problems related to reproductive health behavior, 4) Sexually transmitted diseases and HIV-AIDS, 5) Environmental care for reproductive health. The mapping results show that 50% of teachers have never learned the materials : the structure and function of reproductive organs, the types of sexually transmitted diseases, and the health effects of sexually transmitted diseases. The level of teacher knowledge about reproductive health education was 26.7% including the excellent category, 33.3% good and 36.7% sufficient. Conclusion: Materials health education for junior high school students need to be implemented through various forms of intra and extracurricular learning in junior high school.